Scenekunst i Grønland: Fra projektteatre til Nationalteater - Burkal, Ivan (Peripeti, 2019)
Da de første grønlandske skuespillere vendte tilbage til Grønland fra Tuukkaq Teatret i Fjaltring i 1984 var forventningerne store. På trods af flere tiltag som teaterredegørelsen fra 1996 skulle man helt frem til 2010 inden den første lov blev vedtaget. Loven fastlægger rammerne for Grønlands Nationalteater og den tilhørende skuespilleruddannelse. When the first Greenlandic actors returned to Greenland from the Tuukkaq Theater in Fjaltring in 1984, expectations were great. Despite several initiatives such as the theatrical release from 1996, one had to go all the way up to 2010 before the first law was adopted. The Act lays down the framework for Greenland’s National Theater and the related actor education.